Sacred populations of Cercopithecus sclateri: Analysis of apparent population increases from census counts. Issue 4 (26th November 2013) - Baker, Lynne R.; Tanimola, Adebowale A.; Olubode, Oluseun S.
Abstract The development of effective conservation and management actions for populations of wild species generally requires monitoring programs that provide reliable estimates of population size over time. Primate researchers have to date given more attention to evaluating techniques for monitoring primates in natural habitats compared to populations that occur in villages or urban areas. We conducted censuses to estimate the abundance and density of two sacred, village‐dwelling populations (Lagwa and Akpugoeze) of Sclater's monkey (Cercopithecus sclateri), a threatened species endemic to southeastern Nigeria, and compared these data to previous census results. We recorded population increases in both sites: a 66% increase over 4½ years in Lagwa (from 124 to 206 individuals) at an annual rate of 10.2%, and a 29% increase over 4 years in Akpugoeze (from 193 to 249 individuals) at an annual rate of 5.7%. Mean group size also increased in both sites. Density in Lagwa was 24.2 individuals/km2, and density in a core survey area of Akpugoeze was 36–38 individuals/km2. Our results may have been affected by monkey ranging and grouping patterns and improved detectability due to our revised census technique, which included secondary observers. With further work on methodology for censusing populations that occur in human‐settled environments, techniques can be refined and customized to individual sites for more accurate estimates. Our investigation of Sclater's monkey in Lagwa and Akpugoeze, two sites critical for conservation of the species, indicated that both of these populations have increased, and neither faces immediate risk of extirpation. Such population growth, while encouraging, will likely exacerbate human–monkey conflict and thus should be understood in terms of potential socioeconomic impacts. Am. J. Primatol. 76:303–312, 2014. © 2013 Wiley Periodicals, Inc.